2017
DOI: 10.1364/boe.8.004965
|View full text |Cite
|
Sign up to set email alerts
|

Molecular response of mitochondria to a short-duration femtosecond-laser stimulation

Abstract: The research of mitochondrial dysfunction is of great importance and implicated in a range of neurodegenerative diseases. Traditionally, to investigate mitochondrial dynamics and functions, mitochondria are usually stimulated indirectly by treating cells with exogenous chemicals like oxidative agents. Such treatment lacks precision and controllability, and will simultaneously activate unknown complex cell processes. In this study, we report that two-photon 100-μs line scan by a femtosecond laser can induce res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Since mitochondria are the primary place of ROS generation [21], we further studied the effects of three different irradiance (0.31, 0.62, 0.93 mW/cm 2 ) on mitochondrial function at the dose of 1.12 J/cm 2 . Interestingly, the results are consistent with ROS production.…”
Section: Pbm Resulted In Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Since mitochondria are the primary place of ROS generation [21], we further studied the effects of three different irradiance (0.31, 0.62, 0.93 mW/cm 2 ) on mitochondrial function at the dose of 1.12 J/cm 2 . Interestingly, the results are consistent with ROS production.…”
Section: Pbm Resulted In Mitochondrial Dysfunctionmentioning
confidence: 99%
“…For example, optical tweezers use optical gradient forces to manipulate specific targets 1,2 . Focused pulsed lasers facilitate tasks such as cutting cell membranes for drug delivery 12,13 , disrupting mitochondria functions 14,15 , and inducing cell fusion 16,17 . However, existing manipulation platforms rely on manually delineating targets based on prior knowledge from the sample, lacking the ability for chemical-based automatic target selection, and are unsuitable for highly mobile cellular entities.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of a photoacoustic laser on preimplantation embryos have not, to our knowledge, been reported. Previous studies have reported that intense lasers can induce alterations in DNA, mitochondria, spindle apparatus, as well as cell metabolism and survival (4)(5)(6)(7)(8). Yet, the laser parameters used in those studies differ significantly from the laser parameters used in photoacoustic imaging systems.…”
mentioning
confidence: 99%